Low Flow Analysis On Semenyih River - Liow, Yun Hau (2018)
Prediction pf low flow of a river in magnitude as well as in frequency is necessary for the planning and design of water resource projects since low flow affects significantly in water supply, water quality and river periods of extreme hydrologic events. Semenyih Rive is choose for this study. The objective of this study is to compare and identify the best fitted probability distribution used to carry out low flow analysis. The four probability distribution used in the study were Gumbel Distribution. Weibull distribution, Log-Pearson III distribution and Log-Normal distribution. The daily discharge data was collected from the Department of Irrigation and Drainage ranges from year 1975 to year 2014, 40 years of records. The Kolmogrov-Sminov test and Chi-Squared test were used as the goodness of fit test to choose the best fir probability distribution. Flow Duration Curve method was used to compare with Q710. In overall, Log-pearson type 3 which has a statistical value of 0.08082 and Weibull distribution with 0.01713 are recommended in estimation of low flow discharges for all the rivers under study which can be used in water quality and quantity management.